Professional practice in gender violence approach in the criminal legal field: a psicosocial analysis - Cubells, Jenny; Calsamiglia, Andrea; Albertín, Pilar (Anales de Psicología / Annals of Psychology, 2010)
The main goal in this study is to assess, from a psicosocial point of view, how women are treated in legal institutions, exploring the gender perspective on interactions. It is a qualitative research that uses in-depth interviews, participant observation and discussion groups. The analysis has been made with Grounded Theory, with the support of the program Atlas.ti. The results show an absence of gender perspetive in the legal agents’ practice that treat violence towards women, and its consequences, such as secondary victimization or the professionals’ emotions.